Transforming Intelligence Operations in Indonesia: Challenges and Opportunities in the Digital Age - Al Waro'i, Muhammad Nur Abdul Latif (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
The digital revolution has transformed global intelligence paradigms, making advanced technology essential for modernizing national security systems. This paper discusses the integration of digital technologies, such as Artificial Intelligence (AI), Machine Learning (ML), big data analytics, and cybersecurity, into Indonesia's intelligence operations. Traditionally, Indonesia's intelligence relied on Human Intelligence (HUMINT) and Signal Intelligence (SIGINT), but the rise of digital threats such as cyberattacks, terrorism, and social media-driven radicalization now demands the adoption of advanced technologies to improve detection and response effectiveness. This study uses a qualitative methodology and conducts an extensive literature review of academic articles, policy reports, and case studies to explore the application of digital technologies in Indonesia’s intelligence context. Key findings reveal that, although AI, big data, and other digital tools present significant potential, their integration is hindered by inadequate infrastructure, data privacy and security concerns, and cultural resistance within the intelligence community. The study recommends improving digital infrastructure, strengthening cybersecurity policies, and fostering public-private partnerships and international collaborations to support Indonesia’s intelligence modernization efforts. This research emphasizes the need for continued investment in technology and inter-agency cooperation to enhance Indonesia’s intelligence capabilities, ensuring that the country is prepared to tackle 21st-century security challenges.